Odpowiedź:
f(x)=a(x-x1)(x-x2)
18= a( 10-1)(10-7)
18= 27 a
a= 18/27= 2/3
f(x)= 2/3( x-1)(x-7) = 2/3(x²-8x+7)= 2/3 x²- 16/3 x +14/3
Δ= 256/9-4*2/3*14/3= 256/9 - 112/9=144/9
q=-Δ/4a= -144/9: 4*2/3= -144/9 : 8/3=-144/9*3/8= - 432/72=- 6
ZW= <-6,+∞)
Szczegółowe wyjaśnienie:
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Odpowiedź:
f(x)=a(x-x1)(x-x2)
18= a( 10-1)(10-7)
18= 27 a
a= 18/27= 2/3
f(x)= 2/3( x-1)(x-7) = 2/3(x²-8x+7)= 2/3 x²- 16/3 x +14/3
Δ= 256/9-4*2/3*14/3= 256/9 - 112/9=144/9
q=-Δ/4a= -144/9: 4*2/3= -144/9 : 8/3=-144/9*3/8= - 432/72=- 6
ZW= <-6,+∞)
Szczegółowe wyjaśnienie: